Set-theoretic methods in democratization research: an evaluation of their uses and contributions. Issue 1 (2nd January 2019) - Møller, Jørgen; Skaaning, Svend-Erik
ABSTRACT: Set-theoretic methods in the form of explanatory typologies have for long figured prominently in democratization research, especially in comparative historical analysis. In the 1990s, qualitative comparative analysis (QCA) entered this research field but a tally shows that the number of democratization studies using this method has so far been low and there is little evidence of any take-off. We review a series of landmark studies that use explanatory typologies and 16 studies that use QCA to see how they fare on three criteria: alignment between hypotheses and methods, the strength of causal claims, and the employment of robustness tests. The review shows that most of the QCA applications devote too little attention to formulating set-theoretic propositions and to carrying out robustness tests. Moreover, many scholars are too quick to interpret their findings as causal relationships, especially in light of the modest use of within-case evidence. Finally, it is striking that virtually none of these analyses has influenced the literature in the way some of the studies combining simple explanatory typologies with within-case analysis have. Against this backdrop, we discuss the potential of QCA for democratization research.